Ploidy Determination in the Pathogenic Fungus Sporothrix spp. - Ferreira, Beatriz H.; Ramírez-Prado, Jorge H.; Neves, Gabriela W. P.; Torrado, Egídio; Sampaio, Paula; Felipe, Maria Sueli S.; Vasconcelos, Ana Tereza; Goldman, Gustavo H.; Carvalho, Agostinho; Cunha, Cristina; Lopes-Bezerra, Leila M.; Rodrigues, Fernando (Frontiers in Microbiology, 2019)
The pathogenic clade of the Sporothrix genus comprises the aetiological agents of sporotrichosis, a worldwide emergent disease. Despite the growing understanding of their successful pathogen traits, there is little information on genome sizes and ploidy within the genus. Therefore, in this work we evaluated the ploidy of four species of the Sporothrix genus, specifically S. brasiliensis, S. schenckii, S. globosa and S. pallida. Through cell cycle analysis of the yeast-phase cells, we showed that the DNA content of G0/G1 cells was similar to the genome size determined by whole genome sequencing. Moreover, ploidy of S. schenckii, S. brasiliensis and S. pallida that was determined by allele composition using next generation sequencing data is consistent with monomorphic positions at each allele. These data show that the analyzed strains of Sporothrix are haploid, or at least aneuploid, laying the foundation for the development of a molecular toolbox for Sporothrix spp.